The subdural membrane: unraveling the pathophysiology and treatment of chronic subdural hematoma - Arunachalam Sakthiyendran, Naveen; Gonzalez-Salido, Jimena; Perkins, Teresia; Enriquez-Marulanda, Alejandro; Dasenbrock, Hormuzdiyar; Holsapple, James (Frontiers in Surgery, 2025)
Chronic subdural hematoma (cSDH) is one of the most common neurosurgical conditions, with incidence expected to rise sharply as populations age. Once regarded as a passive sequela of venous rupture, cSDH is now understood as an active, membrane-driven disorder characterized by persistent inflammation, fragile neovascularization, and local fibrinolysis that collectively fuel hematoma expansion and recurrence. This evolving biological model explains the limitations of traditional surgical approaches, which relieve mass effect but do not address the underlying pathophysiology. Burr-hole drainage with subdural drainage remains the gold standard, though recurrence rates approach 10%–20% and perioperative risks are magnified in frail patients. Minimally invasive strategies, such as twist-drill craniostomy and the subdural evacuating port system, expand options for high-risk populations, while mini-craniotomy may benefit complex or organized collections. Emerging adjuvant therapies, including middle meningeal artery embolization, statins, tranexamic acid, and corticosteroids, target the inflammatory and angiogenic milieu; however, results remain heterogeneous, and safety concerns persist. Novel directions such as biomarker-guided patient stratification, anti-VEGF therapies, platelet-rich plasma injection, and endoscopic membranectomy reflect a paradigm shift toward disease-modifying interventions. Collectively, these advances highlight a growing opportunity to personalize treatment, reduce recurrence, and improve long-term outcomes in cSDH.